The Alliance for Progress, modernization theory, and the history of management education: The case of CEPAL in Brazil. Issue 1 (February 2020) - Wanderley, Sergio; Barros, Amon
We investigate the case of the Economic Commission for Latin America in Brazil to discuss how modernization theory was mobilized to influence management education. The theories formulated by the Economic Commission for Latin America formed the basis of the courses it offered on development administration and management and the public administration schools it helped create. The theories from the Economic Commission for Latin America were contrary to US interests and to the modernization theory tenets developed by US scholars. The Alliance for Progress, launched in 1961 by US President J.F. Kennedy, was a project informed by modernization theory aimed to foster development in Latin America, and to contain the spread of Communism after the Cuban Revolution. The Alliance for Progress mobilized a network of US-controlled institutions that invested in management education and in an interpretation of development administration and management based on modernization theory that confronted the Economic Commission for Latin America. We make use of Burke's Pentad to articulate the interactions among (asymmetrical) players at different levels of analysis and along the historical period investigated. We treat science as literature, and we present our analysis in a dramatistic narrative to promote reflexive management learning. We show that US-led investment in management education increased considerably after the launch of the Alliance for Progress, and that it lasted throughout the 1960s.